A crucial role for a node‐localized transporter, HvSPDT, in loading phosphorus into barley grains. Issue 4 (17th March 2022) - Gu, Mian; Huang, Hengliang; Hisano, Hiroshi; Ding, Guangda; Huang, Sheng; Mitani‐Ueno, Namiki; Yokosho, Kengo; Sato, Kazuhiro; Yamaji, Naoki; Ma, Jian Feng
Summary: Grains are the major sink of phosphorus (P) in cereal crops, accounting for 60–85% of total plant P, but the mechanisms underlying P loading into the grains are poorly understood. We functionally characterized a transporter gene required for the distribution of P to the grains in barley ( Hordeum vulgare ), HvSPDT ( SULTR‐like phosphorus distribution transporter ). HvSPDT encoded a plasma membrane‐localized Pi/H + cotransporter. It was mainly expressed in the nodes at both the vegetative and reproductive stages. Furthermore, its expression was induced by inorganic phosphate (Pi) deficiency. In the nodes, HvSPDT was expressed in both the xylem and phloem region of enlarged and diffuse vascular bundles. Knockout of HvSPDT decreased the distribution of P to new leaves, but increased the distribution to old leaves at the vegetative growth stage under low P supply. However, knockout of HvSPDT did not alter the redistribution of P from old to young organs. At the reproductive stage, knockout of HvSPDT significantly decreased P allocation to the grains, resulting in a considerable reduction in grain yield, especially under P‐limited conditions. Our results indicate that node‐based HvSPDT plays a crucial role in loading P into barley grains through preferentially distributing P from the xylem and further to the phloem.